Development of control system for automated guided vehicle (AGV) - Syed Mohd Safwan, Sayed Md Saifuddin (2009)
This thesis is focused on development of the control system for Automated Guided Vehicle (AGV). This thesis concentrates on developing the control system for AGV involve about how the AGV will operate, involve of the movement and loading & unloading mechanism. The objectives of this project are to develop the control system parts involving develop the electronic circuit system and computer program of the system. The wired guided navigation used to communicate the computer to the AGV to ensure the AGV work accordingly. Subsequently, this project needs to be fabricating each of the electronic components to become one complete circuit. All the computer programmings are building by using Code Blocks software, the compiler which is compatible with electronic components and Visual Basic software. Afterwards, Visual Basic 6 is used in this project to create user friendly interface which is better than C interface (Command Prompt). This thesis also includes the test result of control system involving test program and test circuit for the AGV before proceed to the real AGV control system.